A Comprehensive Review on Phage Therapy and Phage-Based Drug Development - Longzhu Cui; Shinya Watanabe; Kazuhiko Miyanaga; Kotaro Kiga; Teppei Sasahara; Yoshifumi Aiba; Xin-Ee Tan; Srivani Veeranarayanan; Kanate Thitiananpakorn; Huong Minh Nguyen; Dhammika Leshan Wannigama (MDPI AG, 2024)
Phage therapy, the use of bacteriophages (phages) to treat bacterial infections, is regaining momentum as a promising weapon against the rising threat of multidrug-resistant (MDR) bacteria. This comprehensive review explores the historical context, the modern resurgence of phage therapy, and phage-facilitated advancements in medical and technological fields. It details the mechanisms of action and applications of phages in treating MDR bacterial infections, particularly those associated with biofilms and intracellular pathogens. The review further highlights innovative uses of phages in vaccine development, cancer therapy, and as gene delivery vectors. Despite its targeted and efficient approach, phage therapy faces challenges related to phage stability, immune response, and regulatory approval. By examining these areas in detail, this review underscores the immense potential and remaining hurdles in integrating phage-based therapies into modern medical practices.